1948
DOI: 10.1172/jci102012
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Clearance of Endogenous “Creatinine” in Man

Abstract: The existing methods for the analysis of inulin, as well as the requirements for the continuous intravenous infusion of this material, place the inulin clearance method for measuring the glomerular filtration rate beyond the reach of practicality for many laboratories and in general limit clearance observations to relatively short intervals of time. There is a requirement for a simpler clearance method of at least approximate accuracy by which observations can be made continuously for periods of 24 hours or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
2

Year Published

1949
1949
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(123 citation statements)
references
References 20 publications
5
116
2
Order By: Relevance
“…Table III shows the data we have collected re-TABLE I Nude, fasting body weights of subjectsfor the three days before, the three days of sodium administration and the three following days garding glomerular filtration rate and sodium and chloride excretion in these normal subjects. In subject E. W. the glomerular filtration rate is estimated from the 24 hour endogenous creatinine clearance (2,3). In our other two subjects, glomerular filtration rate was determined by inulin clearances (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table III shows the data we have collected re-TABLE I Nude, fasting body weights of subjectsfor the three days before, the three days of sodium administration and the three following days garding glomerular filtration rate and sodium and chloride excretion in these normal subjects. In subject E. W. the glomerular filtration rate is estimated from the 24 hour endogenous creatinine clearance (2,3). In our other two subjects, glomerular filtration rate was determined by inulin clearances (4).…”
Section: Resultsmentioning
confidence: 99%
“…Because our studies involved very low and very high rates of sodium and chloride excretion resulting from the marked variations in sodium intake, observations were made to determine, if possible, how glomerular filtration and tubular reabsorption of sodium affected the excretion of sodium by normal subjects. Table III shows the simultaneous 24 hour endogenous creatinine clearance taken as a measure of glomerular filtration rate (2,3) and the simultaneous 24 hour urine sodium and chloride content. Simultaneous inulin clearances and sodium excretions for subjects M. L. and W. C. are also recorded.…”
Section: Displacement Of Intracellular Potassium By Sodiummentioning
confidence: 99%
“…The clear serum was separated and used for biochemical assays. Renal function was assessed by measurement of serum urea (Natelson et al 1951) and serum creatinine levels (Brod and Sirota 1948).…”
Section: Serum Kidney Marker Analysismentioning
confidence: 99%
“…Creatinine clearance in man has therefore usually been found to be higher than inulin clearance, both in health (Miller and Winkler, 1938;Brod and Sirota, 1948;Hare et al, 1949;Smith, 1951 ;Mattar et al, 1952) and in disease (Miller and Winkler, 1938;Brod and Sirota, 1948;Hare et al, 1949;Smith, 1951 ; Mattar et al, Miller et al, 1952 ;Berlyne et al, 1964;Vere and Walduck, 1964 (1938) found that endogenous creatinine clearance was equal to inulin clearance in several normal subjects. In four patients with renal disease, however, the creatinine clearance was greater than inulin clearance (Miller and Winkler, 1938).…”
Section: Introductionmentioning
confidence: 99%